S18: Active Travel as a Sustainable Alternative in Promotion of Health-Enhancing Physical Activity (HEPA) (Baltic Journal of Sport and Health Sciences, 2026)
Rationale: This symposium explores the multifaceted role of active travel – walking and cycling – as an efficacious approach to addressing concurrent global challenges essential for climate action and urban environment for increasing physical activity in children. The symposium will highlight that both walking and cycling are accessible forms of transportation with significant physical, psychosocial, and environmental benefits. However, the adoption and sustainability of these behaviours depend on a complex interplay of individual competencies, environmental quality, perceived safety, and broader social and institutional support from diverse European contexts. It will feature specific case studies and analyses from Germany, Belgium, Switzerland, Czech Republic, and the Netherlands, elucidating effective strategies and key findings related to the promotion of walking and cycling.Purpose: Primary objectives encompass the synthesis of evidence regarding active travel’s efficacy for HEPA promotion, evaluation of impactful policies and infrastructure developments within the selected nations, discussion of contributions towards SDG targets, and identification of barriers and facilitators influencing adoption patterns.Findings: The collection of studies reveal that while cycling interventions in schools can foster healthy habits and environmental awareness, their long-term success requires structural support and integration into daily routines, especially in diverse and underserved communities. Similarly, the quality of the walking environment shaped by factors such as security, lighting, and infrastructure significantly influences walking enjoyment and perceived safety, with seasonal changes presenting additional challenges for maintaining active travel habits throughout the year. Barriers to active transport, such as traffic hazards and unsafe neighbourhood settings, are common concerns, but systematic identification and targeted interventions can lead to improvements in safety and participation.Conclusion: The symposium will also underscore the value of collaborative, cross-sectoral approaches – bridging health and mobility sectors and engaging local stakeholders – to address key barriers, co-design context-specific solutions, and promote equity in access to active travel. By embedding active travel and school-based intervention into daily life activities and urban policy, these initiatives demonstrate potential for reducing health inequalities, enhancing environmental sustainability, and supporting lifelong healthy behaviours among children and the broader community